Accurate modelling of nematic liquid crystal under the combination of microwave signal and applied voltage. Issue 1 (2nd January 2020) - Geng, Jin-Ling; Song, Lizhong
ABSTRACT: In this paper, a three-dimensional modelling of nematic liquid crystal (NLC) under the combined action of applied voltage and microwave signal is presented. The analytical method applied in the modelling is detailed. In previous research, the modelling of liquid crystal usually uses a small signal wave, and neglected its effect on the orientation of liquid crystal. In this paper, we take the microwave signal into consideration in the calculation of liquid crystal orientation, and get the influence of the power of microwave signal on the orientation. The variations of the relative permittivity of liquid crystal E7 with the power of microwave signals at 30 GHz are obtained. This method is applicable for the modelling of NLC under high power signals excitation. Graphical Abstract: